An Assessment of Economic Sustainability in Broiler Enterprises: Evidence from Jordan - Al-Sharafat, Ali; Al-Deseit, Bassam; Al-Masad, Motasem (Asian Journal of Agriculture and Rural Development, 2020)
Assessing economic sustainability is crucial to measure livestock enterprise success. This study is aimed at assessing the economic sustainability of broiler enterprises in Jordan. To achieve the goals of this study, 94 broiler farms were surveyed. A multi-stage sampling technique, descriptive statistics, and simple economic analysis were adopted. The investigated farms’ economic viability, which is the best indication for sustainability, is measured through profitability, liquidity and productivity indicators. The values of the economic sustainability indicators used in this study to assess profitability, liquidity, and productivity showed that the broiler sector in Jordan is economically viable and sustainable. Investors in livestock activities in Jordan are advised to invest in the broiler industry as it is with high economic sustainability.